Optimized correlator for LS codes-based CDMA systems - Pérez, Carmen (2011)
Loosely Synchronized codes, which have gained considerable interest in CDMA-based wireless communications and sensory systems, can be constructed from a set of mutually orthogonal complementary sets of sequences. In this paper a new architecture is provided for the correlation of such codes. It demands less memory and number of operations than previous ones based on efficient correlators for complementary set of sequences, and can be easily implemented in programmable devices due to its regular structure.